Analysis of Perioperative Findings of Cholecystectomy in relation to American Society of Anesthesiologists (ASA) Status - ., Faheem; Ghani, Umar Fayyaz; Shah, Muhammad Yousaf; Gul, Uzma Javed; Qamar, Rohan; Khan, Rashid Iqbal (Pakistan Armed Forces Medical Journal, 2024)
Objective: To analyze the role of ASA status in carrying out laparoscopic cholecystectomies by evaluating the perioperative findings of patients. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital, Rawalpindi Pakistan, from Jan 2019 to Jan 2021. Methodology: Laparoscopic cholecystectomies were performed on 385 patients with symptomatic gallstones. The inclusion criteria comprised of symptomatic cholelithiasis, acute cholecystitis and chronic cholecystitis. Data for the perioperative findings such as gallbladder grades, bile, cystic duct, cystic artery and Common Bile Duct were recorded during the study. Results: The study included 226(59%) female patients and 159(41%) males. The mean age was 48.15±15.5 years. There were 145(37.66%) patients in American Society of Anesthesiologists Classification ASA-I, 174(45.20%) patients in ASA-II and 66(17.14%) in ASA-III. Results showed that the abnormalities of cystic duct were 34(23.4%) in ASA-I, 68(39.1%) in ASA-II and 43(65.2%) in ASA-III. For CBD, they were 7(4.8%) in ASA-I, 49(28.2%) in ASA-II and 44(66.2%) in ASA-III. The complications of cystic artery and bile were 34(23.4%) in ASA-I, 60(34.5%) in ASA-II, 46(69.7%) in ASA-III and 82(56.6%) in ASA-I, 119(68.4%) in ASA-II, 50(75.8%) in ASA-III respectively. The gallbladder grades I were 27(18.6%) in ASA-I and (4.5%) in ASA-III whereas, grades V were 7(4.8%) in ASA-I and 20(30.3%) in ASA-III. Conclusion: Peri-operative morbidity increased with increasing ASA status, therefore, there is a significant relationship between ASA Status and peri-operative findings.